1992
DOI: 10.1203/00006450-199207000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Myopathy Studies on Permeabilized Muscle Fibers1

Abstract: ABSTRACT. Respiratory parameters of skeletal muscle were determined in permeabilized muscle fibers by adapting a technique described by Veksler et al. for cardiac fibers (Biochim Biophys Acta, 892:191-196, 1987). This method consists of the permeabilization of muscle fibers by saponin by allowing respiratory substrates and inhibitors to reach the mitochondria. In this way, the mitochondria may be studied inside the fibers as if they were isolated. We have verified, using various techniques, that the mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…The heart was quickly excised and placed in an ice-cold BIOPS relaxing solution containing 10 mmol l −1 Ca-EGTA buffer, 0.1 µM free Ca 2+ , 20 mmol l −1 imidazole, 20 mmol l −1 taurine, 50 mmol l −1 K-MES, 0.5 mmol l −1 dithiothreitol, 6.56 mmol l −1 MgCl 2 , 5.77 mmol l −1 ATP, 15 mmol l −1 phosphocreatine, pH 7.1 (Veksler et al, 1987;Letellier et al, 1992) before further dissection. The heart was then emptied of blood, the bulbus and atrium removed, and the ventricle was weighed and cut into three parts.…”
Section: Materials and Methods Experimental Animals Temperature Protmentioning
confidence: 99%
“…The heart was quickly excised and placed in an ice-cold BIOPS relaxing solution containing 10 mmol l −1 Ca-EGTA buffer, 0.1 µM free Ca 2+ , 20 mmol l −1 imidazole, 20 mmol l −1 taurine, 50 mmol l −1 K-MES, 0.5 mmol l −1 dithiothreitol, 6.56 mmol l −1 MgCl 2 , 5.77 mmol l −1 ATP, 15 mmol l −1 phosphocreatine, pH 7.1 (Veksler et al, 1987;Letellier et al, 1992) before further dissection. The heart was then emptied of blood, the bulbus and atrium removed, and the ventricle was weighed and cut into three parts.…”
Section: Materials and Methods Experimental Animals Temperature Protmentioning
confidence: 99%
“…After 15-20 min of permeabilization,[60% of the cytosolic lactate dehydrogenase was released from the muscle fibres, while the mitochondrial citrate synthase activity remained\5% in the supernatant. 8,9 Mitochondrial function was quantified by measuring adenosine diphosphate-stimulated oxygen consumption (State 3 respiration) polarographically at 30°C using a Clark-type electrode (Strathkelvin Instruments, Glasgow, UK) connected to a personal computer that displayed the respiration rate value online (949 oxygen System, Strathkelvin Instruments). Adenosine diphosphate-stimulated oxygen consumption reflects the first derivative of the oxygen concentration in time in the respiration chamber and is termed oxygen flux corrected for wet weight muscle tissue (2-5 mg) introduced into the chamber.…”
Section: Rat Modelmentioning
confidence: 99%
“…For instance, we have shown that as low as 30% of the cytochrome c oxidase (COX) activity is sufficient to maintain a normal respiratory rate (Letellier et al, 1992(Letellier et al, , 1993(Letellier et al, , 1994Rossignol et al, 1999). Thus, it is difficult to demonstrate the presence of a deficit in a respiratory chain complex from the polarographic study.…”
Section: Mitochondrial Diseases Statistical Analysismentioning
confidence: 99%
“…Oxygen consumption rate was measured polarographically at 30°C on permeabilized muscle fibers as described in Letellier et al (1992). The respiratory activities (Resp.…”
Section: Biochemical Studymentioning
confidence: 99%
See 1 more Smart Citation